Roadmap for Transforming Preoperative Assessment to Preoperative Optimization. (April 2020) - Aronson, Solomon; Murray, Sutton; Martin, Gavin; Blitz, Jeanna; Crittenden, Timothy; Lipkin, Mike E.; Mantyh, Christopher R.; Lagoo-Deenadayalan, Sandhya A.; Flanagan, Ellen M.; Attarian, David E.; Mathew, Joseph P.; Kirk, Allan D.; et al.
Abstract : Preoperative assessment typically equates to evaluating and accepting the presenting condition of the patient (unless extreme) and commonly occurs only a few days before the planned surgery. While this timing enables a preoperative history and examination and mitigates unexpected findings on the day of surgery that may delay throughput, it does not allow for meaningful preoperative management of modifiable medical conditions. Evidence is limited regarding how best to balance efforts to mitigate modifiable risk factors versus the timing of surgery. Furthermore, while the concept of preoperative risk modification is not novel, evidence is lacking for successful and sustained implementation of such an interdisciplinary, collaborative program. A better understanding of perioperative care coordination and, specifically, implementing a preoperative preparation process can enhance the value of surgery and surgical population health. In this article, we describe the implementation of a collaborative preoperative clinic with the primary goal of improving patient outcomes.